Elucidating the characteristic of leachates released from microplastics under different aging conditions: Perspectives of dissolved organic carbon fingerprints and nano-plastics. (15th April 2023) - Ren, Xiuna; Han, Ye; Zhao, Haoran; Zhang, Zengqiang; Tsui, To-Hung; Wang, Quan
Highlights: The leachates released from MPs under different aging conditions were studied. DOC releasing characteristics were related to MP' type and aging condition. MPs were mainly prone to release protein-like and hydrophilic substances. More small sizes and rough NPs were released in UV-aged treatments. UV irradiation aggravated the toxicity of leachate released from MPs. Abstract: Despite numerous studies that have been devoted to investigating the aging behaviors of microplastics (MPs), dissolved organic carbon (DOC) and nano-plastics (NPs) released from MPs under different aging conditions were limited. Herein, the characterizations and underlying mechanisms of DOC and NPs leaching from MPs (PVC and PS) in the aquatic environment for 130 days under different aging conditions were investigated. The results showed that aging could reduce the abundance of MPs, and high temperature and UV aging generated small-sized MPs (< 100 μm), especially UV aging. DOC-releasing characteristics were related to MP type and aging condition. Meanwhile, MPs were prone to release protein-like and hydrophilic substances except for 60 °C aging of PS MPs. Additionally, 8.77 × 10 9 –8.87 × 10 10 and 4.06 × 10 9 –3.94 × 10 10 NPs/L were detected in leachates from PVC and PS MPs-aged treatments, respectively. High temperature and UV promoted the release of NPs, especially UV irradiation. Meanwhile, smaller sizes and rougher NPs were observed in UV-aged treatments, implying higher ecological risks of leachates from MPs under UV aging. This study highlights the leachate released from MPs under different aging conditions comprehensively, which could offset the knowledge gap between the MPs' aging and their potential threats. Graphical abstract: Image, graphical abstract